Rapid identification of Candida species by FT-IR microspectroscopy - Essendoubi, Mohammed; Toubas, Dominique; Bouzaggou, Mohamed; Pinon, Jean-Michel; Manfait, Michel; Sockalingum, Ganesh D. (Biochimica et biophysica acta, 2005)
Due to the continuous increase of human candidiasis and the great diversity of yeasts of the Candida genera, it is indispensable to identify this yeast as early as possible. Early identification enables an early diagnostic and patient-adapted anti-fungal therapy, thus reducing morbidity and mortality related to these infections. In view of this, we have in this study investigated microcolonies using a method based on Fourier transform-infrared microspectroscopy (FTIRM) for a rapid and early identification of the most frequent Candida species encountered in human pathology. FTIR spectroscopy is a whole-cell “fingerprinting” method by which microorganisms can be identified. By exploiting the huge discriminating capacity of this technique, we identified 6 species ( Candida albicans, Candida glabrata, Candida parapsilosis, Candida tropicalis, Candida krusei, and Candida kefyr) from a collection of 57 clinical strains of Candida, isolated from hospitalised patients. Data obtained on 10- to 18-h-old microcolonies were compared to cultures of 24 h. Our results clearly show the efficiency and the robustness of FTIR (micro)spectroscopy in identifying species with a classification rate of 100% for both microcolonies and 24-h cultures. FTIR microspectroscopy is thus a promising clinical approach, because compared to conventional and molecular techniques, it is time and money saving, has great identification and discriminating potentials, and is amenable to an automated high-throughput routine system.